2018
DOI: 10.1039/c8cc07167e
|View full text |Cite
|
Sign up to set email alerts
|

Rhodium(iii)-catalysed decarbonylative annulation through C–H activation: expedient access to aminoisocoumarins by weak coordination

Abstract: Rhodium-catalysed decarbonylative annulation of isatoic anhydrides with alkynes through C-H activation for the synthesis of aminoisocoumarins was developed. This enables the gram-scale transformation to iodoisocoumarin which is a vital building block in transition-metal-catalysed cross couplings. These compounds exhibit blue-emitting luminescence properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 53 publications
1
8
0
Order By: Relevance
“…293-309) for both bond lengths and angles show that the differences between the two symmetry-independent molecules are of a statistical nature. For both compounds, the bond lengths and angles are close to those observed for a similar structure (Mayakrishnan et al, 2018). In both compounds, there is an intramolecular N-HÁ Á ÁO hydrogen bond present in each molecule forming an S(6) ring motif: see Table 1 and Fig.…”
Section: Structural Commentarysupporting
confidence: 74%
See 1 more Smart Citation
“…293-309) for both bond lengths and angles show that the differences between the two symmetry-independent molecules are of a statistical nature. For both compounds, the bond lengths and angles are close to those observed for a similar structure (Mayakrishnan et al, 2018). In both compounds, there is an intramolecular N-HÁ Á ÁO hydrogen bond present in each molecule forming an S(6) ring motif: see Table 1 and Fig.…”
Section: Structural Commentarysupporting
confidence: 74%
“…amino-1H-isochromen-1-ones gave only one hit, viz. 8-amino-3,4-bis(4-methoxyphenyl)-1H-isochromen-1-one (CSD refcode NIKMAY; Mayakrishnan et al, 2018). The conformation of this molecule is slightly different from that of compound (I).…”
Section: Hirshfeld Surface Analysismentioning
confidence: 99%
“…Recently, Uma Maheswari, Perumal, et al reported the Rh-catalyzed decarbonylative annulation of the less-strained isatoic anhydrides 174 with alkynes for the synthesis of aminoisocoumarins 177 (Scheme ). In this process, the weakly coordinating anhydrides facilitated the C–H activation to deliver the five-membered rhodacyclic intermediate 175 . Subsequent protonation and cyclization led to C–N bond cleavage and the formation of intermediate 176 , which underwent decarbonylation, insertion of the alkyne, and reductive elimination to afford the desired products 177 .…”
Section: Decarbonylation With Cleavage Of the C(acyl)–o/c(acyl)–c Bondsmentioning
confidence: 99%
“…Similarly, Perumal and coworkers reported a regioselective decarbonylative cyclization of readily available isatoic anhydride 275 and an alkyne to afford biologically important 8-aminoisocoumarin 277 catalyzed by Rh complex (Scheme 45). [50] Electron-poor alkynes reacted slowly with a lower yield than electron-rich alkynes. A directed ortho-CÀ H activation of the rhodium complex generated a metalacycle intermediate 275 a.…”
Section: Addition To Coà X Bondmentioning
confidence: 99%